Development of Biocompatible Coatings for Dental Implants Based on Transition Metal Nitrides - Alexei Yumashev (Journal of Global Pharma Technology, 2019)
Nitrides are nitrogen (N) compounds with other chemical elements, in particular with transition metals. For transition metal nitrides, the main ones are properties such as homogeneity of the material of nitride products, high electrical conductivity, and high melting points, with hardness exceeding most other known materials. As experimental samples we used ready transition metals alloys from cylinders, 10 mm in diameter, and 20 mm in height. 10 cylinders for each alloy were used. Heating to the required temperatures was carried out using an induction heating furnace. Temperatures were measured with a DT model pyrometer, the measuring range of which ranges from -50 to + 110 °C, with an error of one tenth of a °C. Alloys were studied using electron microscopy, and the hardness of the resulting alloy was also measured. In addition to the samples of implants with a nitride coating, samples of cast products (implants) were produced. 10 samples of each type were made. The nitride film present almost doubled the hardness indices of metals and their alloys. The smallest wear out was observed for gold and platinum samples, the largest - for zirconium, titanium and nickel, 2-3 times more (p≤0.05). The presence of even the thinnest titanium nitride film changed these indicators, as a result of which the wear out level became even lower than that of gold (p≤0.05). The present nitride film prevents the formation of an adsorption layer. Such implants wear out will be slowed down in comparison with metal ones, but without a nitride film, on which an adsorption layer is formed. Along with the preference of titanium physical and chemical properties over other metals and their alloys, the deposition of a titanium nitride film is a necessary property to improve. Titanium has several advantages over other metals, including lower thermal conductivity and resistance to corrosion changes. Titanium nitride gives maximum hardness and maximum wear resistance. Nitride film implants acquire no damage; moreover, nitride spraying can also be used with other types of implants, for example, ceramics. The nitride film gives the metal base additional stability properties, creating a protective layer. The combined use of a titanium implant with titanium nitride spraying (layer thickness no more than 0.1 mm) increases the properties of hardness and wear resistance of implants.Keywords: Nitrogen (N) compounds; Transition metals alloys; Electrical conductivity; Dentistry; Dental implants.